Determinants of divergent Salmonella and Shigella epithelial colonization strategies resolved in human enteroids and colonoids - Petra Geiser; Maria Letizia Di Martino; Ana C. C. Lopes; Alexandra Bergholtz; Magnus Sundbom; Martin Skogar; Wilhelm Graf; Kajsa Björner; Johan Vessby; Dominic-Luc Webb; Per M. Hellström; Jens Eriksson; et al. (mBio)
ABSTRACT Despite their relatedness, Salmonella and Shigella enteropathogens differ in infectious dose, pathogenesis, and disease kinetics. The prototype strains Salmonella enterica serovar Typhimurium (Salmonella) and Shigella flexneri (Shigella) use Type-3-secretion-systems (T3SSs) to colonize intestinal epithelial cells (IECs). However, they have evolved unique sets of T3SS effectors and accessory virulence factors. A synthesis of how these differences impact the temporal progression of infection in non-transformed human epithelia is missing. Here, we followed Salmonella and Shigella infections of human enteroids and colonoids by time-lapse imaging to pinpoint virulence factor modules that shape the divergent epithelial colonization strategies. By an apical targeting module that integrates flagella and the SPI-4-encoded adhesin system with T3SS-1, Salmonella accomplishes appreciable numbers of apical IEC invasion events. These are promptly counteracted by IEC death, thus fostering a polyclonal iterative epithelial colonization strategy. The lack of a corresponding apical targeting module in Shigella makes this pathogen reliant on external factors, for example, preexisting damage, for rare apical access to the intraepithelial environment. However, Shigella compensates for this ineptness by an intraepithelial expansion module reliant on the tight coupling of OspC3-dependent temporal delay of cell death and IcsA-mediated mobility. This module enables intraepithelial Shigella to evade the IEC death response just long enough to expand laterally, thus fostering an essentially monoclonal colonization strategy. Taken together, the study reveals how a small set of virulence factors shapes divergent epithelial colonization strategies by related enterobacteria.IMPORTANCEPathogenic bacteria employ partially overlapping sets of virulence factor functions to colonize host epithelia but can differ markedly in their pathogenesis and disease kinetics. This work combines bacterial genetics and real-time microscopy in enteroids and colonoids to decipher the divergent colonization strategies of Salmonella enterica Typhimurium and Shigella flexneri—two major enteropathogens—in non-transformed human intestinal epithelia. The results reveal how virulence factor modules enabling efficiency at either the invasion step (Salmonella) or the intraepithelial expansion stage (Shigella) drive the radically different infection cycles of these related enterobacteria. Moreover, our work emphasizes how real-time studies in infection models that retain primary host cell features are critical to understanding infectious disease progression.